Simbolisme Agama dalam Politik Islam - Ibnu Rochman (Jurnal Filsafat "WISDOM", 2003)
The study of the symbolism of religion in Islamic politic is necessary to conduct because it is vast opportunity avaliable in the reformation and democratization era for most of Indonesian representing Moslem to express thier insight and thought that various forms ranging from vulgar, the emotion and the rational one. There are among the expression using symbols, even many Moslem who are active in practical politics Islamic symbols.Considering the title of the study "the Symbolism of Religion Philosophy in Islamic Politic", the author will study the philosopher suggesting that human being is homo symbolicum and also the history of politics in Islam since the disciples of Muhammad to the present. It is expected that the method of study provide the finding that symbolism of religion in Islamic politic takes place not only at present, but also it evidences that human being is homo symbolicus.The study is literature study. The collected data is critically analyzed using interpretation and historical methods. The result of the study shows that the Moslem politicans in the history of Islamic politics used religious symbols in practice. The position of the symbolic action in religion representing the medium of human-cosmic commucation and the physical and spiritual religious communication, are also used in political practice